STANDARDS FOR THE CONSERVATION AND RECOVERY OF EARTHEN HERITAGE, PERU AND CHILE - Vargas-Neumann, Julio (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
This paper presents relevant criteria used in two important oficial Standards that guide intervention to earthen built heritage in Peru and Chile: 1) the revision of Peruvian Standard NTP E-080 and presentation of Seismic Resistant Conservation Principles for Earthen Heritage; and 2) the Chilean Standard for Structural Intervention in Earthen Heritage Construction. Both cases arise for the irst time in either country. In Latin America, these principles or standards cover a huge gap in the regulations for the design of the maintenance and repair of heritage buildings damaged by earthquakes. A new and indispensable element has been the integration of risk management techniques to disasters, through international declarations and charters for heritage conservation. It foresees the inclusion of social organization in national plans for disaster, as well as the treatment for earthen built heritage, during the three stages: Mitigation Emergency and Recovery. Unlike what was commonly done in the past, it is of paramount importance to stop any attempts at heritage demolition, damaged during the emergency phase of an earthquake. Therefore, the importance of a pre-demolition or intervention study and the condition of the heritage building is emphasized, to assess the signiicance of its cultural values and to deeply identify its structural stability. Regulations highlight the vulnerability of earthen material and its tendency to sudden collapse threatening the lives of the occupants or visitors. It also emphasizes the desirability of using criteria based on performance design, which means installing permanent reinforcement to control the movement in damaged heritage structures. However, the use of such reinforcement must meet three conditions: 1) Minimal intervention, to preserve its heritage signiicance; 2) Compatibility with earthen material, to prevent deterioration due to the reinforcement itself; and inally, 3) Reversibility, to modify or withdraw the erinforcement when better solutions are available.